Elevated expression of USP9X correlates with poor prognosis in human non-small cell lung cancer - Wang, You; Liu, Yu; Yang, Bo; Cao, Hong; Yang, Chun-Xu; Ouyang, Wen; Zhang, Shi-Min; Yang, Gui-Fang; Zhou, Fu-Xiang; Zhou, Yun-Feng; Xie, Cong-Hua (Journal of Thoracic Disease; Vol 7, No 4 (April 28, 2015): Journal of Thoracic Disease, 2015)
Background: The aim of this study was to investigate the expression of ubiquitin-specific peptidase 9, X-linked (USP9X) in non-small cell lung cancer (NSCLC) patients and to evaluate the relevance of USP9X expression to tumor prognosis. Methods: Ninety-five patients who underwent surgical resection for clinical stage I-IIIA NSCLC between July 2008 and July 2011 were included in this study. Immunohistochemical analysis of USP9X expression was performed on 95 NSCLC tissues and 32 adjacent normal lung parenchymal tissues from these patients. The Chi-squared test was used to compare the clinicopathological characteristics between different groups. Kaplan-Meier analysis and a Cox regression model were used to determine the independent prognostic factors. A P value